2015
DOI: 10.1002/pbc.25810
|View full text |Cite
|
Sign up to set email alerts
|

Improving Care for Children With Cancer in Low- and Middle-Income Countries-A SIOP PODC Initiative

Abstract: The Paediatric Oncology in Developing Countries (PODC) committee of International Society of Paediatric Oncology (SIOP) has 10 working groups that provide a forum for individuals to engage, network, and implement improvements in the care of children with cancer in low-and middle-income countries. The development of adapted guidelines (medulloblastoma, retinoblastoma, Wilms tumor, neuroblastoma, retinoblastoma, Burkitt lymphoma, supportive care), advocacy and awareness (on hospital detention and essential drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
(58 reference statements)
1
35
0
4
Order By: Relevance
“…Socio‐economic hardship is the main contributor to the abandonment of cancer treatment in LMIC and includes financial and transportation difficulties, lack of medical insurance, loss of formal employment due to treatment, lack of coverage of essential drugs, and family disintegration . We found that almost 20% of families came from rural settings, which may indicate that they were from households with insufficient income to cover their basic needs, according to the World Bank estimations.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Socio‐economic hardship is the main contributor to the abandonment of cancer treatment in LMIC and includes financial and transportation difficulties, lack of medical insurance, loss of formal employment due to treatment, lack of coverage of essential drugs, and family disintegration . We found that almost 20% of families came from rural settings, which may indicate that they were from households with insufficient income to cover their basic needs, according to the World Bank estimations.…”
Section: Discussionmentioning
confidence: 80%
“…Most reports about cancer treatment outcomes in LMIC lack abandonment data, although formal recommendations recognize that it is important to analyze abandonment in two ways: as an event (relapse or death) and as censored, considering that upper and lower limits will reflect the true event‐free survival estimate. Adequate treatment abandonment reporting would assist in designing strategies that decrease abandonment and improve treatment outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional sample of LMIC nurses from Africa, Latin America, and Asia indicated a similar need for specialty training and curriculum development (17). The importance of education and learning is underscored by the development of an Education and Training Working Group in SIOP PODC which aims to facilitate training and education of health-care providers in LMICs (18). This case study adds to the growing body of evidence showcasing the importance of specialty nurse training in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, recommendations have been evidence based, but when published evidence to guide regimen selection was not available, as is often the case in the most resource‐limited settings, expert opinion was used. Four of these guidelines (Wilms tumor, Kaposi sarcoma, Burkitt lymphoma, and supportive care) were designed for settings in low‐income countries where only the minimal requirements for treatment with curative intent are available (defined as setting 1, see Table ). However, for some cancers, definition of an overall level of care was insufficient to select the best treatment regimen, because they depend on access to a particular component of care, such as neurosurgery for brain cancers or radiation therapy for unresectable sarcomas.…”
Section: Introductionmentioning
confidence: 99%